2011
DOI: 10.1021/jo2012797
|View full text |Cite
|
Sign up to set email alerts
|

Revision of the Absolute Configurations of Bethosides B and C and Their Aglycone

Abstract: The absolute stereochemistry of the steroidal saponins bethosides B and C was previously assigned as (22R,25R) on the basis of work that employed Horeau's method. Our studies of helosides A and B created doubt about both the original assignment and consequently our conclusion that relied upon it. The absolute configurations of bethosides B and C are revised to (22S,25R) following X-ray crystallographic analysis of their aglycone. Synthesis and full spectral characterization of both the 22R and 22S aglycones is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
12
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 14 publications
3
12
0
Order By: Relevance
“…Careful analysis of these spectra revealed differences for the NMR data of the side chains of these two compounds. The proton and carbon data of the side chain of compound 8 were superimposable with those of bethosides B and C earlier described by Challinor et al [11] and thus confirming the stereochemistry (22S, 25R) for compound 8. The differences observed mostly concerned C-23 C-22, C-21 and C-20 (Table 1), and careful analysis in comparison with those of bethosides B and C [11] revealed that the orientation of the OH group at C-22 in compound 1 is α (22R) rather than β (22S), as in compound 8.…”
supporting
confidence: 86%
See 1 more Smart Citation
“…Careful analysis of these spectra revealed differences for the NMR data of the side chains of these two compounds. The proton and carbon data of the side chain of compound 8 were superimposable with those of bethosides B and C earlier described by Challinor et al [11] and thus confirming the stereochemistry (22S, 25R) for compound 8. The differences observed mostly concerned C-23 C-22, C-21 and C-20 (Table 1), and careful analysis in comparison with those of bethosides B and C [11] revealed that the orientation of the OH group at C-22 in compound 1 is α (22R) rather than β (22S), as in compound 8.…”
supporting
confidence: 86%
“…The differences observed mostly concerned C-23 C-22, C-21 and C-20 (Table 1), and careful analysis in comparison with those of bethosides B and C [11] revealed that the orientation of the OH group at C-22 in compound 1 is α (22R) rather than β (22S), as in compound 8. The similarity of the NMR data of C-25, C-26 and C-27 for compound 1, 8 and bethosides B and C [11] indicated that the stereochemistry at C-25 (25R) is identical for these compounds. The identification of D -glucose and L -rhamnose, including their absolute configurations, was carried out by direct HPLC analysis of the hydrolysate obtained after the acid hydrolysis of compound 1 with 1 M HCl.…”
mentioning
confidence: 99%
“…Based on their 13 C NMR resonances ( δ C 73.4 for 22- R and δ C 75.5 for 22- S ), the configuration at C-22 was assigned as R in 2 . 17 The sugars and their positions in 2 were found to be similar to those of 1 . The 1 H and 13 C NMR spectroscopic data assignment in 2 (Table 1) was based on gHSQC, gHMBC (Fig.…”
Section: Resultsmentioning
confidence: 79%
“…The S -configuration at C-22 was inferred by comparing its NMR data with those of the S and R stereoisomers. 13,17 The sugars were identified as glucose by co-TLC (EtOAc-CHCl 3 -MeOH-H 2 O, 6:4:4:1) of standard sugars from Sigma-Aldrich with the sugar mixture obtained via acid hydrolysis of 1 . Both glucose units were found to be β based on the characteristic coupling constant values of their anomeric protons ( J = 7.7 Hz (H-1′) and J = 7.8 Hz (H-1″)) in the 1 H NMR spectrum.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation